Stabilizace břehů nádrží - Podola, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Předmětem této bakalářské práce je posouzení břehů nádrže Bystřička z hlediska vzniku abraze. Posudek je zaměřen na 2 hlavní body na severovýchodním břehu nádrže nedaleko od přítoku. Jedná se o oblast v blízkosti hotelu Beskydská Tatranka. práce je zakončena návrhem vybraných biotechnických opatření ke zpomalení či zastavení narušování břehů.

The subject of this bachelor’s thesis is assessment of reservoir banks Bystřička in terms of abrasion. Judgement is focused on two main points on the northeastern bank of the reservoir near the tributary. It is an area near the hotel Beskydská Tatranka. Thesis is finished with design of selected biotechnical measures to slow or stop erosions banks.
Stabilization of bank
Keywords: abraze; břeh; nádrž; stabilizace; abrasion; bank; reservoir; stabilization